1991
DOI: 10.1002/food.19910350208
|View full text |Cite
|
Sign up to set email alerts
|

Protein digestibility in dog. Effect of the quantity and quality of dietary fat (virgin olive oil and sunflower oil)

Abstract: Protein digestibility has been estimated in dog when fed on two similar diets except their lipid quality (virgin olive oil and sunflower oil) from weaning up to 6 months of life. Experiments were carried out at 60, 105 and 150 days of adaptation to either diet. In dog, age does not seem to affect the protein digestive and metabolic utilization when fed on a high lipid content diet. A higher dietary fat percentage led to an increase of the mentioned parameters which could be caused to a delayed gastric emptying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Moreover, diets with olive oil have been shown to lower the exocrine pancreatic secretion in dogs, while enhancing utilization of certain nutrients, such as proteins. 78,79 This effect is related to the action of oleic acid with respect to the stimulation-inhibition balance of pancreatic secretion, 80 and to other benefits at the gastrointestinal level. 81 The health-promoting effects of olive oil consumption have been related traditionally to its high oleic-acid content.…”
Section: Brief History Of the Research On Olive Oil And Health: Evidementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, diets with olive oil have been shown to lower the exocrine pancreatic secretion in dogs, while enhancing utilization of certain nutrients, such as proteins. 78,79 This effect is related to the action of oleic acid with respect to the stimulation-inhibition balance of pancreatic secretion, 80 and to other benefits at the gastrointestinal level. 81 The health-promoting effects of olive oil consumption have been related traditionally to its high oleic-acid content.…”
Section: Brief History Of the Research On Olive Oil And Health: Evidementioning
confidence: 99%
“…Olive oil also reduces hypertension, 69 improves thrombogenic conditions, 72,73 prevents or improves diabetes, 74 reduces inflammatory processes, 75,76 and alleviates intestinal inflammatory illness, 77 in addition to promoting effects related to the MUFA (oleic acid) content. Moreover, diets with olive oil have been shown to lower the exocrine pancreatic secretion in dogs, while enhancing utilization of certain nutrients, such as proteins 78,79 . This effect is related to the action of oleic acid with respect to the stimulation‐inhibition balance of pancreatic secretion, 80 and to other benefits at the gastrointestinal level 81 …”
Section: Brief History Of the Research On Olive Oil And Health: Evidementioning
confidence: 99%
“…The secretion of bicarbonate, total protein, amylase, lipase and chymotrypsin followed the same pattern as the pancreatic flow rate. Parallel experiments conducted in these very same animals during the adaptation period revealed that, while there were no differences between groups VOO and SO in fat digestibility (Ballesta et al, 1990b), an improved protein digestive and metabolic utilization was actually evidenced in VOO animals (Ballesta et al, 1991). Hence, pancreatic adaptation to diets containing olive oil as dietary fat source seems to represent a key advantage in terms of exocrine pancreatic economy, at least in this species.…”
Section: Exocrine Pancreatic Secretionmentioning
confidence: 86%